Xenophobic sentiments: the meeting point of julio-claudian rome and ramaphosa’s South Africa (2020)
Migration of people to various places is a permanent feature of human history. For example, shifting from a nomadic economy to a system based on food production in the past allowed people to settle permanently in a place and hold claim to it. Such a situation is known to have induced creation of group identity and led to stereotype relationship between host communities and foreign migrants with far reaching effects. Xenophobia, an age old phenomenon, is one of the products of the stereotype. This paper goes back in time to review xenophobic sentiments in Rome during the reign of the Julio-Claudian emperors in which large numbers of foreign migrants were attracted to Rome due to the empire’s economic prosperity and opportunities for wealth creation. In doing this, the paper digs up the forms, causes, patterns, and consequences of xenophobic actions. Then, following an exploration of contemporary South-African xenophobic sentiments, which match closely with the Romans’, the work makes a comparative assessment to find sociological parallels between the ancient and modern states which share common hopes for the migrants. The paper particularly identifies xenophobia as a form of social depravity that requires all moral strength to root it out.